If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2w + -6) + 2(w) = 3(w + 8) Reorder the terms: 2(-6 + 2w) + 2(w) = 3(w + 8) (-6 * 2 + 2w * 2) + 2(w) = 3(w + 8) (-12 + 4w) + 2(w) = 3(w + 8) Combine like terms: 4w + 2w = 6w -12 + 6w = 3(w + 8) Reorder the terms: -12 + 6w = 3(8 + w) -12 + 6w = (8 * 3 + w * 3) -12 + 6w = (24 + 3w) Solving -12 + 6w = 24 + 3w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-3w' to each side of the equation. -12 + 6w + -3w = 24 + 3w + -3w Combine like terms: 6w + -3w = 3w -12 + 3w = 24 + 3w + -3w Combine like terms: 3w + -3w = 0 -12 + 3w = 24 + 0 -12 + 3w = 24 Add '12' to each side of the equation. -12 + 12 + 3w = 24 + 12 Combine like terms: -12 + 12 = 0 0 + 3w = 24 + 12 3w = 24 + 12 Combine like terms: 24 + 12 = 36 3w = 36 Divide each side by '3'. w = 12 Simplifying w = 12
| 4(a-3)= | | 9+3x=8x+12 | | X(90)=1050+375 | | (u+4)*10= | | 95.30=19.95+0.55x | | -5x-2(4-2x)=2+7 | | 15+.20m=25.00+.10m | | x+8+16=0 | | (q-5)*2= | | -5-2(4-2x)=2+7 | | 2x+44=x-12 | | 2(w-6)+2(w)=3(w+8) | | (e+5)*4= | | 0.5(2n+6)=0.2(8n-10) | | Y+-12=11 | | 5.95+0.06m=30 | | 4+11y-1=9y+21-7y | | 8(X-4)=350 | | 42-4X=200 | | 1-x=.4 | | 1.5(x+8)=5.7+0.6x | | 5x+113=11x-7 | | 2x-(5x+2)=9x-26 | | 3y-5=-8(6+5t) | | 11(t-3)+3t=7(2t+4)-10 | | 4x-7=-2x-19 | | 8.99(85)=650+x | | 6+25x=20x+8 | | 8(x-5)-6x=-26 | | 0.5x(y-z)= | | 5.45=14.8-2.2t | | -22=4w+2(w+4) |